Organic amendments drive shifts in microbial community structure and keystone taxa which increase C mineralization across aggregate size classes. (February 2021) - Wang, Xiaoyue; Bian, Qing; Jiang, Yuji; Zhu, Lingyue; Chen, Yan; Liang, Yuting; Sun, Bo
Abstract: Organic amendments can stimulate soil organic carbon (SOC) mineralization and soil aggregation simultaneously, which can improve C sequestration and soil fertility. However, the microbial mechanism governing C mineralization at the aggregate level remains uncertain. Here, we investigate how long-term organic amendments change SOC mineralization via affecting the microbial community composition and their co-occurrence pattern from micro-to macroaggregates. Four fertilization regimes from an 8-year field experiment were selected to study this mechanism, i.e., no fertilization (CK); inorganic NPK fertilizer (NPK); NPK + straw (NS); and NPK + straw and manure (NSM). Our results indicated that organic amendments significantly modified the C dynamics, bacterial and fungal community composition and network topological patterns in all aggregate sizes. Specifically, for microbial community composition, organic amendments increased the relative abundance of most Gram-negative bacteria and saprotrophic fungi. For microbial network relationships, organic amendments shifted keystone taxa from oligotrophs to copiotrophs in the bacterial network, and from Eurotiales to Sordariales in the fungal network, respectively. In addition, organic amendments alleviated competitive interactions coupled with keystone taxa in the bacterial network. These microbial changes were responsible for the increase of C mineralization in all aggregates, but the dominant microbial mechanisms varied with aggregate size. The alleviated competitive interactions coupled with keystone taxa of the bacterial network dominated the increases of C mineralization in macroaggregates, while the bacterial community composition did so in microaggregates. However, the fungal community composition only showed a significant impact on altering C mineralization in macroaggregates. Overall, our study provides a fundamental understanding of the microbial regulation of C dynamics at the aggregate level and highlights the importance of network topological patterns. Highlights: Organic amendments and aggregate size both affected microbial properties and Cmin. Topological properties of bacterial networks affected Cmin in macroaggregates. Bacterial community composition dominated the changes of Cmin in microaggregates. Fungal community composition only affected Cmin in macroaggregates.